A guide to design the trajectory of active particles: From fundamentals to applications. (October 2022) - Al Harraq, Ahmed; Bello, Mustapha; Bharti, Bhuvnesh
Abstract: Active particles convert external energy into motility, displaying a variety of dynamical features. Recent progress in the field has marked a shift in focus from understanding the origin and sources of active motion to controlling the dynamics and trajectory of individual microswimmers. This review explores the advancements made in a two-fold perspective—the role of particle design and that of external factors. Our main goal is to highlight the guiding principles, which determine active particle trajectory. These include, on the one hand, the role of the morphology of active particles and their assemblies in driving translation, rotation, and corresponding coupling between the two. On the other hand, the effect of environmental parameters such as the presence of physicochemical heterogeneities including interfaces, suspended obstacles, and boundaries on the modality and trajectory of active colloids. We discuss the potential of using active particles in biomedical and environmental applications through recent examples. Graphical abstract: Image 1